Why Are Our Women-Composers So Little Known?: Concerning Women’s Musical Output in Poland Between the Two World Wars - Lindstedt, Iwona (Musicology today (Warsaw), 2019)
Polish women-composers of the interwar period (1918–1939) have not been the subject of adequate research so far. We only have some contributory publications and general surveys dedicated to their output. This paper presents the initial results of a study that aims at creating a more multi-sided, in-depth picture of women-composers’ work, including their participation in local and international music life as well as their achievements in the field of composition, the styles and genres practised by selected representatives of this milieu. The paper also discusses the reception of these phenomena in the press of the period. My research leads me to the conclusion that, despite functioning in a kind of ‘parallel world’ in relation to the virtually all-male domain of music composition ‘proper’, the Polish women-composers did penetrate into that world, contributing to its dominant trends and tendencies, from Romantic inspirations to musical modernism, as well as popular music. Their contributions need to be taken into account if we wish fully to reconstruct and appreciate the Polish music created in that period.